Mediating role of Innovation and Moderating Role of Size of Enterprise over the Relationship between Entrepreneurial Orientation and Performance of Micro and Small Enterprises - Riyadh Mahmood, Yousif; Dekhn Hamzah, Khitam (International Journal of Engineering and Technology, 2018)
In this study the authors tried to identify mediating role of innovation and moderating role of size of enterprise in the relationship between entrepreneurial orientation and performance of Micro and Small Enterprises (MSEs). The researchers also investigated the effect that vary from enterprise size that basically means micro and small enterprises. For the purpose of this study data was collected from 384 MSE's operating in Punjab province. Initially the data was analyzed using SPSS 22 and later on for the development of structure equation modeling Smart PLS-3 was used. Only two aspects of entrepreneurial orientation have been analyzed; first one is risk taking and second one is pro-activeness, third most common aspect innovation has been taken as mediating variable as an enterprise cannot be innovative if it has not the capacity of risk taking and pro-activeness. These both aspects are attached to performance and also deals with innovation. The major contribution of the study is to identify any moderating effect of size of the enterprise over the relationship between entrepreneurial orientation, innovation and performance of MSEs. These elements basically show the contribution that is made by the innovation and performance of the MSE's. The objectives of the study were achieved, and it was found that there is no difference between performance of MSEs on the basis of entrepreneurial orientation and innovation. It is proved that the size of the enterprise is not the factor. The linkages found are affected by size of the enterprises.Â
Keywords: Entrepreneurship; Innovation; Micro and small enterprises; Performance; Risk taking.